Questionnaire survey on maternal pertussis vaccination for pregnant women and mothers in Nara prefecture, Japan - Taito Kitano; Tomoko Onishi; Masahiro Takeyama; Midori Shima (Taylor & Francis Group, 2020)
Background: Infantile pertussis is a major concern and causes a significant health burden worldwide. Maternal adult tetanus, diphtheria, and acellular pertussis (Tdap) vaccination is very effective way of preventing infantile pertussis. However, Tdap has not been approved by the Japanese government or been included in Japan's national immunization program (NIP). We carried out a questionnaire survey to investigate whether Japanese women would accept the Tdap vaccination if they were provided with appropriate information. Methods: The questionnaire survey was administered to pregnant women who visited the Obstetrics and Gynecology Department and mothers who visited the Pediatrics Department of Nara Medical University, Kashihara City, Japan, between October 2018 and May 2019. The questionnaire included information about pertussis infection and maternal vaccination, followed by seven questions. Results: A total of 943 participants answered the questionnaire (481 pregnant women and 462 mothers). Before reading the information, just 4.6% of participants knew that infantile pertussis can be prevented by maternal vaccination. After reading the information, 93.0% and 92.6% of participants thought that the maternal Tdap vaccine should be approved by the Japanese government and be included in the NIP, respectively. Although only 67.6% of participants wished to have the maternal Tdap vaccine without government financial support after reading the information, 92.5% said they would have the vaccine with government support (P < .001). Conclusion: Most Japanese mothers and pregnant women would like the maternal Tdap vaccine to be approved by the government and included in the NIP, once they have been provided with appropriate information.